The guest : a novel [compact disc, unabridged] - Cline, Emma (Random House Audio, 2023)
Summer is coming to a close on the East End of Long Island, and Alex is no longer welcome. A misstep at a dinner party, and the older man she's been staying with dismisses her with a ride to the train station and a ticket back to the city. With few resources and a waterlogged phone, but gifted with an ability to navigate the desires of others, Alex stays on Long Island and drifts like a ghost through the hedged lanes, gated driveways, and sun-blasted dunes of a rarified world that is, at first, closed to her. Propelled by desperation and a mutable sense of morality, she spends the week leading up to Labor Day moving from one place to the next, a cipher leaving destruction in her wake.